2008
DOI: 10.1111/j.1744-6570.2008.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Teamwork Processes: Tests of a Multidimensional Model and Relationships With Team Effectiveness Criteria

Abstract: Drawing from Marks, Mathieu, and Zaccaro (2001), we proposed that narrowly focused teamwork processes load onto 3 higher‐order teamwork process dimensions, which in turn load onto a general teamwork process factor. Results of model testing using meta‐analyses of relationships among narrow teamwork processes provided support for the structure of this multidimensional theory of teamwork process. Meta‐analytic results also indicated that teamwork processes have positive relationships with team performance and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
739
3
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 776 publications
(787 citation statements)
references
References 190 publications
30
739
3
15
Order By: Relevance
“…Another limitation of our study is that we focused on team coordination, yet prior research suggests there is a broader range of team processes that can contribute to team performance (LePine, Piccolo, Jackson, Mathieu, & Saul, 2008;Marks et al, 2001). For example, it is possible that different types of goals influence not only coordination, but also strategy formulation and planning processes, as well as emergent states, such as collective efficacy (DeRue, Hollenbeck, Ilgen, & Feltz, 2010;Marks et al, 2001;Weldon et al, 1991;Weldon & Weingart, 1993).…”
Section: Goal Setting In Teams 26mentioning
confidence: 99%
“…Another limitation of our study is that we focused on team coordination, yet prior research suggests there is a broader range of team processes that can contribute to team performance (LePine, Piccolo, Jackson, Mathieu, & Saul, 2008;Marks et al, 2001). For example, it is possible that different types of goals influence not only coordination, but also strategy formulation and planning processes, as well as emergent states, such as collective efficacy (DeRue, Hollenbeck, Ilgen, & Feltz, 2010;Marks et al, 2001;Weldon et al, 1991;Weldon & Weingart, 1993).…”
Section: Goal Setting In Teams 26mentioning
confidence: 99%
“…Earlier studies have also revealed the importance of feedback and reflection for professional growth. [12,13,23] Besides simulation, other joint education options can be useful when seeking to promote nurse-practical nurse collaboration in clinical nursing. [39] Focusing on generic competencies besides technical skills in multi and transprofessional education has been suggested to enhance effective team work and patient safety in health services.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7,23] To sum up, all the dynamic interaction, collaboration, coordination and management processes occurring in teams have an effect on patient safety and quality, and also on worker satisfaction and feelings of success. [10][11][12][13] In consequence, teamwork is one of the essential skills that can and should be practiced to promote collaboration and reduce errors. [23,24] Successful multiprofessional teamwork has the benefits of combining skills and knowledge, crossing boundaries and creating effective networks to develop a more client-centered approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations